Exploration on Student Project Cases with Power Electronics Converter Application - Hishammudin, Muhammad Sharul Nizam; Zulkifli, Shamsul Aizam; Zawawi, Nadzirah (Evolution in Electrical and Electronic Engineering, 2021)
This project is to explore the capability of Universiti Tun Hussein Onn Malaysis (UTHM) student especially in FKEE to apply the power electronics converter in simulation application. It has been conducted during the Final Year Program on COVID19 situation in year 2020. The single phase inverter model has been modeled for the first case. This inverter used current control feedback model. As for the second case, it is to control of voltage controlled feedback for the bidirectional DC-DC converter system. The bidirectional model is to charge the battery and then to discharge back to the load. Both projects using the Proportional Integral (PI) controller in order to minimize the error between the target and output signal. From the inverter result part, the input current reference is set at 2A and the output the current reference also at 2A where it shows the controller is working. As for the second projects, in various input and output voltages during the charging and discharging mode at the battery have been observed. At the end, the students have managed to complete and understand the important of power electronics converters.